ABOUT FACTOR, CONDITIONNING PROCESS OF THE TRANSPORT CHANNELFORMING SEDIMENTS - A. V. Magomedova; M. R. Magomedova (Вестник Дагестанского государственного технического университета: Технические науки)
In given article on base of the analysis of the literary sources and generalization experimental and натурных given are elaborated main factors, influencing upon process of the transport channel-forming sediments. The Process of the transport channel-forming sediments is one of the complex physical processes, conditioned by ensemble factor: an hydrоmechanical of the features of the water flow and physico-mechanical features alluvium that is a reason of the absence to united theory of this process, difficulties of the multiple accounting methods of the determination of the consuptionsediment and big divergence in result calculation on him.